ANALISIS DIFUSI INOVASI DAN PENGEMBANGAN BUDAYA KERJA PADA ORGANISASI BIROKRASI - Rusmiarti, Dewi Ariningrum (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
Government effort towards upgrading the work performance of Civil Servants has been implemented in the Bureaucratic Reformation program. Referring to the Presidential Regulation number 81, 2010 about the Grand Design of the 2010â 2025 Bureaucratic Reformation and the Minister for the Empowerment of State Apparaturs Regulation and Bureaucratic Reformation number 20, 2010 about the Road Map of the 2010-2014 bureaucratic Reformation, which covers the Arrangement of the Apparaturs Human Resources Management System through work culture. The adoption process of work culture by the Civil Servants applies the Diffusion Innovation Process theory of Everett M. Rogers. The evaluation of the process implementation applies the structural concept model of Howard Greenbaum. The research uses qualitative approach, along with the case study research strategy. The result of this research reveals the uses of communication channels, time frame dimension, and the importance of the leadersâ behaviour and commitment for Civil Servants (PNS) in order to adopt and change their behaviour and way of thinking which are more appropriate to the standard work culture that holds true. The evaluation of communication channels of the diffusion innovation process influences the organization goals. The evaluation aims at the continuous diffusion innovation process to change the Civil Servantsâ behaviour.